2012
DOI: 10.5209/rev_sjop.2012.v15.n1.37343
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Spanish Human System Audit Short-Scale of Transformational Leadership

Abstract: The aim of this research is to examine the psychometric properties of a Spanish version of the Human System Audit transformational leadership short-scale (HSA-TFL-ES). It is based on the concept of Bass developed in 1985. The HSA-TFL is a part of the wider Human System Audit frame. We analyzed the HSA-TFL-ES in five different samples with a total number of 1,718 workers at five sectors.Exploratory Factor Analysis corroborated a single factor in all samples that accounted for 66% to 73% of variance. The interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…Yet its dimensionality has been questioned (Bycio et al, 1995), and Berger et al (2012) showed that transformational leadership can be measured as a unidimensional construct. Thus, we used the German version of the HSA-TFL short-scale (8 items, Cronbach's α = 0.93).…”
Section: Methodsmentioning
confidence: 99%
“…Yet its dimensionality has been questioned (Bycio et al, 1995), and Berger et al (2012) showed that transformational leadership can be measured as a unidimensional construct. Thus, we used the German version of the HSA-TFL short-scale (8 items, Cronbach's α = 0.93).…”
Section: Methodsmentioning
confidence: 99%
“…This scale has good psychometric properties (Berger, Yepes, & Quijano, 2007;Berger, Romeo, Yepes, & Guardia, 2012) with Cronbach"s α coefficient of .95. The HSA-TFL Short-scale is a one-dimensional scale for screening based on Bass" (1985) four theoretical dimensions with eight items, two for each theoretical dimension: individualized consideration, intellectual stimulation, inspirational motivation, and idealized influence.…”
Section: Instrumentsmentioning
confidence: 99%
“…Taking into account the current situation of a serious economic crisis in the healthcare sector at large, being efficient in given strategic goals has acquired a crucial importance (Berger, Romeo, Guardia, Yepes & Soria, 2012). In this context, the qualitative results allow us to describe the current leadership in the CHS and lead us to ponder whether this is truly leadership or if we are talking about simple management of these entities.…”
Section: Discussionmentioning
confidence: 99%